Field notes contributed by Joseph P. Schaufenbuel, September 29, 1977 - Schaufenbuel, Joseph P.et al (1977)
List of birds and locations contributed by Joseph P. Schaufenbuel. The field notes include an attached report of bird sightings contributed by Thomas K. Shires. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed